2016
DOI: 10.1002/2015jd024583
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing changes in diurnal temperature range: A new data set and characterization of data biases

Abstract: It has been a decade since changes in diurnal temperature range (DTR) globally have been assessed in a stand-alone data analysis. The present study takes advantage of substantively improved basic data holdings arising from the International Surface Temperature Initiative's databank effort and applies the National Centers for Environmental Information's automated pairwise homogeneity assessment algorithm to reassess DTR records. It is found that breakpoints are more prevalent in DTR than other temperature eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…In general, global studies of surface temperatures have found daily minimum temperatures to be increasing faster than daily maximums and winter temperatures to be increasing faster than summer temperatures, resulting in reduced diurnal and seasonal temperature ranges [24][25][26][27]. The most recent Intergovernmental Panel on Climate Change report concluded with medium confidence that globally, daily minimum temperatures have increased more than daily maximum temperatures since 1950 [28].…”
Section: Discussionmentioning
confidence: 99%
“…In general, global studies of surface temperatures have found daily minimum temperatures to be increasing faster than daily maximums and winter temperatures to be increasing faster than summer temperatures, resulting in reduced diurnal and seasonal temperature ranges [24][25][26][27]. The most recent Intergovernmental Panel on Climate Change report concluded with medium confidence that globally, daily minimum temperatures have increased more than daily maximum temperatures since 1950 [28].…”
Section: Discussionmentioning
confidence: 99%
“…The same trends were also observed in Saudi Arabia from 1981 to 2010 (Nazrul Islam et al, ), the mountain stations in the Koshi River Basin (Shrestha et al, ) from 1901 to 2003 (Rai et al, ) and Serbia from 1981 to 2010 (Ruml et al, ). These results were seemingly consistent with the trends in DTR that have been observed since 1979, when global changes in DTR became insignificant (Thorne et al, , 2016b). However, in Xinjiang (China), due to the significant increase in TMIN, DTR decreased significantly on an annual scale, particularly during summer and winter.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are qualitatively in agreement with those obtained with the Pairwise Homogeneity Assessment algorithm (Thorne et al ., ); in particular, we find more frequent breakpoints (i.e. shorter homogeneous periods) for DTR than for the other variables.…”
Section: Data Production Methodsmentioning
confidence: 99%
“…In global datasets, the large amount of data limits the usability of most of these methods. The Pairwise Homogeneity Assessment (Menne and Williams Jr, ) is one of the few examples of breakpoint detection methods that have been applied to global datasets (e.g., Lawrimore et al ., ; Dunn et al ., ; Thorne et al ., ).…”
Section: Introductionmentioning
confidence: 99%